Farce Majeure: The Clinton Administration's Sudan Policy 1993-2000 by David Hoile (London: The European-Sudanese Public Affairs Council, 2000. 120 pages.) (American Journal of Islam and Society, 2002)
One of the fundamental principles of justice is that no accusation be allowed to stand unless there is sufficient evidence to support the allegation. Butsuch principles do not seem to get in the way of propagandists in their mission to discredit. Nobody knows this better than the Sudanese government. And no one has written more on Sudan's plight than Dr. David Hoile, the director of the European-Sudanese Public Affairs Council. Farce Majeure is a comprehensive critique, based largely on Hoile's previously published articles, of the Clinton administration's Sudan policy. Hoile, who has specialized in Sudanese issues for several years, argues that the Clinton administration succeeded in two areas with respect to its policy: preventing a peaceful resolution of the Sudanese civil war, and succeeding in the propaganda war, at least in North America. Hoile then explores how and why this was achieved and helps the reader to understand how Sudan moved from being an insignificant African state, at least from a western vantage point, into a nation constantly in the international limelight. Chapter I provides a good, albeit brief, analysis of the evolving rela tionship between the US and Africa's largest country, since its independence in 1956. Granted that the book's focus is the period from 1993 to 2000, readers could have benefited from a more extensive discussion of the historical context. In chapters I and 5 the author identifies what may be at the root of American aversion to Sudan: ...